Can the Kerlan-Jobe Orthopaedic Clinic Shoulder and Elbow Score Be Reliably Administered Over the Phone? A Randomized Study. Issue 8 (13th August 2018) - Erickson, Brandon J.; Chalmers, Peter N.; Newgren, Jon; Malaret, Marissa; O'Brien, Michael; Nicholson, Gregory P.; Romeo, Anthony A.
Background: The Kerlan-Jobe Orthopaedic Clinic (KJOC) shoulder and elbow outcome score is a functional assessment tool for the upper extremity of the overhead athlete, which is currently validated for administration in person. Purpose/Hypothesis: The purpose of this study was to validate the KJOC score for administration over the phone. The hypothesis was that no difference will exist in KJOC scores for the same patient between administration in person versus over the phone. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: Fifty patients were randomized to fill out the KJOC questionnaire either over the phone first (25 patients) or in person first (25 patients) based on an a priori power analysis. One week after the patients completed the initial KJOC on the phone or in person, they then filled out the score via the opposite method. Results were compared per question and for overall score. Results: There was a mean ± SD of 8 ± 5 days between when patients completed the first and second questionnaires. There were no significant differences in the overall KJOC score between the phone and paper groups ( P = .139). The intraclass correlation coefficient comparing paper and phone scores was 0.802 (95% CI, 0.767-0.883; P < .001), with a Cronbach alpha of 0.89. On comparison of individual questions, there were significant differences for questions 1, 3, and 8 ( P = .013, .023, and .042, respectively). Conclusion: The KJOC questionnaire can be administered over the phone with no significant difference in overall score as compared with that from in-person administration.